Development and quality control of Anti-Age base with oil from Vitis sp. (Research, Society and Development, 2021)
The phytocosmetics potential of natural actives from the Brazilian flora against the pharmaceutical market is unquestionable. Large companies are always looking for new actives and formulations that can provide their customers with care to fight aging and repair damage caused by senescence. In this context of innovation, the objective of this research was the production of an anti-age formulation containing oil from Vitis sp. and assess its preliminary stability. The oil was obtained from a certified supplier, in order to guarantee the quality of the products for cosmetic purposes. Subsequently, samples were prepared at a concentration of 1%. 3% and 5% oil in the O/W formulation. Based on the national manuals of good cosmetic production practices, organoleptic, pH, density, thermal stress and centrifugation analyses were followed. All analyzes were performed in triplicate on days 1 and 12 of the test. The formulations were stable to thermal stress and to the centrifugation test. Regarding density, they presented final values ​​of 1.46 gml-1 ± 0.12, 1.48 gml-1 ± 0.01 and 1.49 gml-1 ± 0.15 respectively for the formulations of 1%, 3% and 5%. Another analysis performed was the pH where results were found of 4.55 ± 0.01, 4.56 ± 0.14, 4.58 ± 0.16 respectively for the formulations of 1%, 3% and 5%. The analysis values ​​suggest a formulation that was stable under thermal stress and a preliminary stability evaluation that has the function of accelerating any instability process of the formulations. Thus, the O/W formulation elaborated is an interesting product to be produced, due to its simplicity. This favors a possible second stage of this research, such as the expansion of stability and physicochemical assessments, microbiological assessment and investigation of therapeutic activities. Although the literature has information on the biological activities of Vitis sp, tests to investigate the biological activities of the formulation and chemical profile need to be carried out to further deepen the topic.